Chronic traumatic encephalopathy is not a real disease. (30th August 2018) - Randolph, Christopher
Abstract: There was a long-lasting debate during the first half of the 1900s about whether boxers suffered from a condition called "dementia pugilistica". This included arguments as to whether there was such a distinct clinical condition, whether it was static or progressive, and whether boxers were actually at any increased risk of any neurological issues at all. The debate was never resolved, but was resuscitated in 2005 with the speculation that a similar condition, dubbed "chronic traumatic encephalopathy (CTE)" existed in retired National Football League (NFL) players. A specific pattern of p-tau deposition has been identified in the brains of NFL retirees, and also identifiable in the brains of at least a percentage of individuals exposed to contact sports in general. Advocates of CTE as a disease describe it as presenting with behavioral disturbance, increased suicidality and neurodegeneration leading to dementia. The evidence to date, however, does not rise to the level of a verifiable disease, and remains at the level of case report. To assume that CTE pathology represents a neurodegenerative disease flies in the face of a number of facts, including that traumatic brain injury does not cause neurodegeneration, protein deposits in the brain are a poor predictor of behavioral symptoms, p-tau is not necessarily toxic or self-propagating, and retired NFL players are actually much physically and mentally healthier than men of their demographic background. They have an all-cause mortality rate that is 50% of that expected, and a suicide rate that is 40% of that expected. The most parsimonious explanation of the evidence to date is that repetitive head trauma may result in p-tau deposition, but that this isoform of p-tau is inert and has no toxic or self-propagating effects.